2020
DOI: 10.1016/s2468-1253(20)30271-5
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes following SARS-CoV-2 infection in liver transplant recipients: an international registry study

Abstract: Summary Background Despite concerns that patients with liver transplants might be at increased risk of adverse outcomes from COVID-19 because of coexisting comorbidities and use of immunosuppressants, the effect of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection on this patient group remains unclear. We aimed to assess the clinical outcomes in these patients. Methods In this multicentre cohort study, we collected data on patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
324
3
6

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(361 citation statements)
references
References 18 publications
13
324
3
6
Order By: Relevance
“…Early published case series in LT and solid organ transplant (SOT) recipients with coronavirus disease 2019 (COVID-19) reported a high fatality rate of up to 30%, exceeding the rate of the general population [ [1] , [2] , [3] , [4] ]. In contrast, a more recent Swiss case study and an international registry study found mortality rates comparable to those of comorbidity-matched non–transplant recipients [ 5 , 6 ]. Initial symptoms of patients with COVID-19 are diverse [ 7 ].…”
mentioning
confidence: 99%
“…Early published case series in LT and solid organ transplant (SOT) recipients with coronavirus disease 2019 (COVID-19) reported a high fatality rate of up to 30%, exceeding the rate of the general population [ [1] , [2] , [3] , [4] ]. In contrast, a more recent Swiss case study and an international registry study found mortality rates comparable to those of comorbidity-matched non–transplant recipients [ 5 , 6 ]. Initial symptoms of patients with COVID-19 are diverse [ 7 ].…”
mentioning
confidence: 99%
“…In contrast, Webb et al [ 52 ] published a study with 151 patients who received LTX. In this study, after LTX patients had no higher risk for a severe disease course.…”
Section: Covid-19 and Liver Damagementioning
confidence: 99%
“…Although historically there have been anxieties that vaccination in transplant recipients may lead to the development of alloimmunity and graft rejection, no clinical evidence has emerged to support this. 12 Although liver transplant recipients have comparable rates of COVID-19-related mortality to the matched general population, 13 they do have higher rates of admission to intensive care and may have been relatively more protected throughout the pandemic due to enhanced social distancing or shielding. Therefore, we still believe this group remains a vulnerable population and should be prioritised for vaccination, with the likely benefits far outweighing the potential risks.…”
mentioning
confidence: 99%